Strategi Bauran Pemasaran Rumput Laut Eucheuma cottoni di Kecamatan Mandalle Kabupaten Pangkep - Herlinawati Herlinawati; Muhammad Bibin; Damis Damis (Cenderawasih University, 2023)
This study aims to determine the marketing mix strategy for Eucheuma cottoni seaweed in Mandalle District, Pangkep Regency. This seaweed is one of the main commodities of Pangkep Regency from the fisheries sector. The main obstacles faced by seaweed cultivators are marketing and price stability. This research is important as information material for cultivators, entrepreneurs and the government in pursuing this business. The research was conducted from December to February 2023, in Mandalle District, Pangkep Regency. The study population consisted of all 207 Euchuma cottoni cultivators. Determination of the number of samples using the slovin formula with the number of samples selected 70 people. To find out which cultivators were sampled, a simple random sampling technique was used. Data collection was carried out using interviews, observation, questionnaires, and focus group discussions. Data analysis using SWOT analysis. The results showed that the new marketing of Euchuma cottoni seaweed in Mandalle sub-district, namely: continuing to provide seeds at affordable prices and providing counseling in stages, optimizing seaweed production, increasing the potential of seaweed already exist, provide training in stages, expand, and maintain marketing networks, increase product selling prices and access to capital.